1988
DOI: 10.1139/b88-166
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhizal status, root anatomy, and phenology of plants in a sugar maple forest

Abstract: The phenology, root anatomy, and mycorrhizal colonization of vascular plant species occurring in a hardwood forest site were studied. Sugar maple (Acer saccharum), the dominant tree, ash (Fraxinus americana), another important tree, and the most abundant herbaceous plants were examined periodically. Most of the herbaceous species present were highly colonized by vesicular–arbuscular mycorrhizae (VAM), but some consistently had low levels of VAM, or were nonmycorrhizal, and several had orchid mycorrhizae. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
1
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(160 citation statements)
references
References 0 publications
4
153
1
2
Order By: Relevance
“…From the present work, it appears that the soil borne spores were not involved in this MSI enhancement. This result agrees with previous studies in which it has been attested that the AM mycelia network is the main source of inoculum in semiarid and arid ecosystems (Brundrett and Kendrick 1991;Bashan et al 2000). Table 6.…”
Section: Originssupporting
confidence: 92%
“…From the present work, it appears that the soil borne spores were not involved in this MSI enhancement. This result agrees with previous studies in which it has been attested that the AM mycelia network is the main source of inoculum in semiarid and arid ecosystems (Brundrett and Kendrick 1991;Bashan et al 2000). Table 6.…”
Section: Originssupporting
confidence: 92%
“…At present we do not know at what time infection becomes established in the plants studied here. Moreover, we were only able to take one mycorrhizal sample at the end of the season and a number of authors have demonstrated seasonal changes (Gay et al, 1982;Brundrett & Kendrick, 1988). The timing of infection and its relevance to soil P could be important and we are currently examining mycorrhizal infection and soil phosphorus levels in a ruderal community at regular intervals, in order to answer these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Old dead roots are an important source of inoculum for glomeromycete fungi which can survive as endophytes in living roots for up to 10 years after arbuscules have collapsed, presumably functioning as inoculum reservoirs for subsequent generations of roots (Brundrett & Kendrick, 1988). These fungi also have a necrotrophic phase when host roots die, providing the fungus with first access to nutrients that can be transferred to hyphae in other plants (Eason, Newman & Chuba, 1991).…”
Section: (5 ) Variable Associationsmentioning
confidence: 99%